Argon storage and diffusion in Earth's upper mantle. (15th May 2019) - Delon, Rémi; Demouchy, Sylvie; Marrocchi, Yves; Bouhifd, Mohamed Ali; Cordier, Patrick; Addad, Ahmed; Burnard, Pete G.
Abstract: In this study, fine-grained polycrystalline olivine was doped with argon at static high pressure (0.30 ± 0.01 GPa) and high temperature (1050 ± 25 °C) conditions during 24 h in a Paterson press, and analysed using a step-heating extraction protocol coupled with noble gas mass spectrometry to investigate argon storage and diffusivity in Earth's upper mantle. Our results show that a single diffusion mechanism controlled argon diffusion in our samples during the step heating experiments. Effective Ar diffusion in olivine has a low activation energy, implying that argon diffusivity is governed by both grain boundary and lattice diffusion. Mean values of lattice diffusion parameters obtained from our results and by reprocessing literature data are E a  = 166 ± 44 kJ mol −1 and D 0  = 10 −7.04 ± 1.13  m 2 ·s −1, and grain boundary diffusion parameters determined from our data are E a  = 22 ± 5 kJ·mol −1 and D 0  = 10 −12.87 ± 0.3  m 2 ·s −1 . Isotopic diffusivity ratios were constant and close to the values determined by Graham's law in the C-regime (i.e., bulk diffusion dominated by grain boundary diffusion) and A-regime (i.e., bulk diffusion controlled by grain boundary and lattice diffusion in proportion to the segregation of Ar between those sites), but varied in the B-regime (i.e., bulk diffusion controlled by both grain boundary and lattice diffusion in a complex manner), implying a higher isotopic fractionation in the kinetic B-regime. Extrapolation to typical mantle grain sizes implies that around 22% of the argon in the upper mantle can be stored at grain boundaries and that effective diffusion is mostly in the A-regime, suggesting a low isotopic fractionation and diffusivities faster than lattice diffusivities alone. The consideration of grain boundaries as a potential Ar storage site can modify equilibrium during partial melting and significantly enrich a liquid in Ar during fluid percolation. The grain size dependence of Ar storage and diffusivity highlights the underestimated role of grain boundaries in the upper mantle, especially in zones of reduced grain size (via dynamic recrystallization) possibly followed by fluid percolation and/or partial melting, such as in subduction zones or below oceanic ridges.